SEASONAL ICE VELOCITY CHANGES AT SOUTH PATAGONIA ICEFIELD - Johnson Gavilan, Erling John; Floricioiu, Dana; Krieger, Lukas; Cardenas Mansilla, Carlos Alberto (My University, 2024)
We estimate the seasonal impact in the ice velocity of the entire South Patagonian Icefield (SPI), the velocity mosaics from 2016 (Winter/Autumn), 2017(Summer/Spring) and 2018(Summer/Spring) were combined to obtain acceleration and deceleration maps. Additionally, a more detailed study was made for seven glaciers in particular, the freshwater Upsala, Viedma, Moreno, O'Higgins and the tidal influenced Pio XI, Jorge Montt, Amalia.
Keywords: glacier velocity; glaciological season